2006
DOI: 10.1163/156854106778877857
|View full text |Cite
|
Sign up to set email alerts
|

Linking soil properties and nematode community composition: effects of soil management on soil food webs

Abstract: The purported benefits of conservation tillage and continuous cropping in agricultural systems include enhancement of soil ecosystem functions to improve nutrient availability to crops and soil C storage. Studies relating soil management to community structure allow the development of bioindicators and the assessment of the consequences of management practices on the soil food web. During one year (December 2003-December 2004), we studied the influence of continuous cropping (CC), intermittent fallow (F), stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(37 citation statements)
references
References 46 publications
1
33
0
3
Order By: Relevance
“…Different letters indicate significant differences (p < 0.05) among treatments or Growing seasons × Sampling times interaction according to Tukey test. of predators and omnivores (Sánchez-Moreno et al, 2006). Hánel (2010) found that Aporcelaimellus increased in abandoned fields, and this taxon was one of the most common at the beginning of our study.…”
Section: Discussionmentioning
confidence: 49%
“…Different letters indicate significant differences (p < 0.05) among treatments or Growing seasons × Sampling times interaction according to Tukey test. of predators and omnivores (Sánchez-Moreno et al, 2006). Hánel (2010) found that Aporcelaimellus increased in abandoned fields, and this taxon was one of the most common at the beginning of our study.…”
Section: Discussionmentioning
confidence: 49%
“…terised by several trophic behaviour and respond readily to environmental changes thus playing an important role in soil food web (Neher, 2001;Sánchez-Moreno et al, 2006). In this system different groups of trophic nematodes are closely correlated with other soil organisms whose activities affect primary production, soil matter decomposition, energy flows, cycle of nutrients, especially nitrogen and phosphorus cycles (Sochová et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Since bacterial feeders, known to influence soil mineralisation, are usually abundant in cultivated soils while predators and omnivores often disappear with cultivation (Fu et al 2005;Wardle et al 1995), the results obtained may therefore be typical of those found in agricultural soils. Natural areas are known to support lower nematode diversity, when compared with cropped fields (Neher et al 2005;Sánchez-Moreno et al 2006). In this study, a maximum of ten nematode families were found in soils from Faro and Guarda, and in the other regions, nematodes were grouped in eight to nine families.…”
Section: Trophic Group Familymentioning
confidence: 58%